MOCVD growth of ZrN thin films on GaN/Si templates and the effect of substrate temperature on growth mode, stress state, and electrical properties. (6th October 2022) - Chen, Qingqing; Yang, Shaoyan; Li, Chengming; Yao, Weizhen; Liu, Xianglin; Niu, Huidan; Yang, Rui; Li, Huijie; Wei, Hongyuan; Wang, Lianshan; Wang, Zhanguo
Abstract: Zirconium nitride (ZrN) is a candidate for contact metal and diffusion barrier in ohmic contacts for GaN-based devices due to its superior electrical conductivity and corrosion resistance. This paper reported ZrN films deposited on GaN/Si templates using metal-organic chemical vapor deposition (MOCVD) and analyzed the effect of substrate temperature ( T s ) on its growth mode, film stress, as well as electrical properties. Firstly, the surface morphology and film roughness of the resultant ZrN epilayers were investigated, which were found to vary dramatically with T s . Then, a temperature-dominated crystal formation process was reasonably proposed, revealing the transfer from the island to layer growth mode and the augmentation of the growth rate of ZrN with elevated T s . Stress information was obtained from the position of XRD diffraction peaks, indicating large in-plane lattice stretching in ZrN film and the presence of compressive stress in the GaN/Si template. The stress states can be related to island merger and thermal mismatch between ZrN and GaN, which proved satisfyingly advantageous in preventing the GaN layer from cracking during the subsequent preparation procedure. In addition, XPS surface and interface investigations were performed to identify the chemical state and the atomic content of the ZrN film, which also implied a relatively clear interface between the ZrN epilayer and GaN/Si template. Furthermore, Hall tests proved the resistivity of ZrN thin film can reach a minimum of 2.28 × 10 −4 Ω cm, owing to the grain boundary chaining and flat film surface at high temperatures. Overall, it appears to have promising prospects for its application in the contact layer and diffusion barrier of ohmic contact in GaN-based devices.